The triumph of the dark : European international history 1933-1939 - Steiner, Zara (Oxford history of modern Europe., 2010)
Following on from her acclaimed study of the collapse of international security during the early 1930's, Zara Steiner gives an account of the coming catastrophe. She shows that the era of Hitler's rise to power, an ascent bent on war, was founded on ideologies which the democratic perceptions could neither penetrate nor arrest.